The response to violence against women and fear of violence and the coping strategies of women in Corregidora, Mexico. (January 2023) - Garfias Royo, Margarita; Parikh, Priti; Walker, Julian; Belur, Jyoti
Abstract: This paper explores women's perceptions of sources of vulnerability to Violence Against Women (VAW) in urban public spaces and their response to this violence. The urban space of Corregidora municipality in Querétaro, Mexico was used as a case study. First-hand data on different types of VAW was gathered through 7 focus group discussions held with 50 women. The Socio-Ecological Framework (SEF) was used to analyse VAW at different levels, using a Social Construction of Space lens as a supportive conceptual framework to explore women's experience of VAW in public spaces. A Crime Prevention Through Environmental Design approach was used to develop targeted recommendations at each level of the SEF. The results show that improvements in infrastructure could be a way forward to prevent VAW in public spaces, such as the provision of lighting, reducing narrow access routes, sidewalks improvement and prioritisation of pedestrian mobility, rather than leaving the burden of responsibility of personal safety and protection to women. Highlights: Women's vulnerability sources can be categorised into personal, socio-cultural or situational Women adopt different coping mechanisms to increase personal protection Coping strategies include time-space avoidance, physical defence, environmental responses and other active measures Violence Against Women is under-reported and invisibilised by official figures There is potential to address Violence Against Women at community and social levels through urban improvement